(untitled) (Bangladesh Journal of Child Health, 2022)
Wilson disease also known as hepatolenticular degenerationis an autosomal recessive disorder of copper metabolism, usually presents either with hepatic or neurological features. But sometimes along with common features, some atypical presentations may also co-exist. We report here two cases of Wilson disease, a 15 years old girl and 14 years old boy presented with some neurological manifestations along with gradual darkening of whole body. BANGLADESH J CHILD HEALTH 2021; VOL 45 (2) : 124-127